Food consumption among overweight and obese working Malay women in urban settings - Ismail, Suriani; Shamsuddin, Khadijah; Abdul Latiff, Khalib; Abu Saad, Hazizi (Medip Academy, 2016)
Background: The Malaysian Dietary Guideline 2010 (MDG) helps Malaysian to objectively estimate their food consumption. This study looks into the type of food consumed in a group of overweight and obese Malays women and the influences of their socio demographic characteristics. Methods:This cross-sectional study was conducted among 140 Malay women with body mass index (BMI) ≥25.0 kg/m2, working in public offices in two urban areas in Malaysia. Their food consumption was monitored using a 7-day self-administered food diary developed based on MDG 2010. The mean numbers of servings were compared to the servings recommended in the MDG 2010 for women who were not physically active, and then the association with socio demographic characteristics was tested using independent t test. Results: Their food consumption compared to MDG recommendations were as follows: 79.8% for carbohydrate, 24.8% for vegetables and fruits, 112.5.0% for protein and 124.0% for milk and dairy products. The consumption of fruits and vegetables was higher in the higher education group (P=0.03), of protein was higher in the high income group (P=0.02) and of milk and dairy product was higher in the younger age group (≤40 year old) (P=0.05). Conclusions:Their consumption of protein and dairy product was higher but the consumption of carbohydrate and vegetables and fruits, was lower than the recommended quantity. The type of food consumption was influenced by respondents’ education level, income and age group.